Realistic health care simulation scenario: what is relevant for its design? - Regina Mayumi Utiyama Kaneko; Maria Helena Baena de Moraes Lopes
ABSTRACT We sought to describe the stages of scenario development with emphasis on the most relevant aspects according to the literature and guidelines of The International Nursing Association for Clinical Simulation and Learning and Best Evidence Medical Education, which are discussed and exemplified on the basis of our professional experience. The following stages were described and commented on for scenario design: planning, objectives, simulation structure and format, case description and perception of realism, pre-debriefing, debriefing, evaluation, materials and resources, and pilot test. A scenario design based on good practices involves important elements, and each stage is closely interrelated and interdependent in its creation process.